Neurocysticercosis in a preschool-age child: case report - MARCIO M. VASCONCELOS; MARCIA REGINA S. RAMOS; PRISCILA JORDAIM SCHWAN; ROMEU DOMINGUES; KELLY CRISTINA T. DANTAS ALENCAR; GESMAR HADDAD HERDY (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis is a frequent cause of epilepsy and other neurologic abnormalities in all age groups, however by virtue of its prolonged incubation period as well as young children's nutritional habits, it is rarely seen in preschool-age children. The objective of this study is to report the case of a 2 ½ year-old child who presented with new-onset seizures. Her diagnostic features, including neuroradiologic findings, are described and compared with the literature. No matter how young he or she may be, every child who presents with new-onset seizures or other unexplained neurologic features and whose CT or MRI shows cystic lesions or contrast-enhancing rounded lesions should raise a suspicion of neurocysticercosis.